Body image and its associated factors in patients with breast cancer with mastectomy at King Chulalongkorn Memorial Hospital. - Cheewabantherng , C.; Roomruangwong , C. (Chulalongkorn Medical Journal, 2023)
Background : Previous studies showed that among postoperative breast cancer patients, loss of their breasts could provoke depression and anxiety that might caused a loss to body image. However, until now, the studies which focused directly on the perception of body image in this group of patients were still sparse. We aimed to study the issue to improve our understanding and to improve the quality of care in breast cancer patients. Objective : To examine body image as well as its associated factors among patients with breast cancer who underwent mastectomy at King Chulalongkorn Memorial Hospital. Design : A cross-sectional descriptive study. Setting : King Chulalongkorn Memorial Hospital. Materials and Methods : Data were collected form 126 patients with breast cancer who underwent mastectomy at King Chulalongkorn Memorial Hospital. Self-report included: 1) General background; 2) Medical history about breast cancer; 3) Body Image Scale (BIS); 4) Jalowiec Coping Scale; 5) Social support questionnaire; 6) Quality of Life questionnaire, 7) Problem and conflict solving questionnaire were completed by the patients. Univariate analysis and multivariate analysis were used to examine associated factors as well as the predictors of body image in this group of patients. Results : Most subjects (56.3%) perceived moderate level of their body image. There were 5 factors, namely; age, level of education, two domains of quality of life (response to surgical treatment and response to nutrition treatment), and coping (emotionfocused domain) were significantly associated with body image (p < 0.01). Conclusion : Perception of body image in this population is similar to other studies. Several studies have found that breast cancer patients treated by surgery are perceived moderate of body image. Knowing the associated factors will aid medical personnel to easily detect and provide support for risk group of patients.